Distribution of serogroup specific antibodies against leptospirosis in livestock in Odisha - BALAMURUGAN, V; VEENA, S; THIRUMALESH, S R A; ALAMURI, A; SRIDEVI, R; SENGUPTA, P P; GOVINDARAJ, G; NAGALINGAM, M; HEMADRI, D; GAJENDRAGAD, M R; RAHMAN, H (The Indian Journal of Animal Sciences, 2017)
The study was conducted to identify epidemiological sero-distribution of Leptospira serovars representing serogroups of antibodies in Odisha, Eastern part of India. Samples were collected from livestock during 2011-2014. A total of 537 non-purposive random serum samples from 12 districts in Odisha were tested at 1:100 dilutions in microscopic agglutination test (MAT) using live antigens of 18 reference Leptospira serovars. The overall prevalence of 36.69% (197/537) with 36.13% in cattle, 54.28% in buffaloes, 28.33% in goats and 44.44% in sheep was observed. Out of 197 reacted sera, 100 samples showed reactivity with more than one serovars representing 50.76% prevalence of multiple serovars. On analysis, the seroprevalence of leptospirosis in cattle (·2 = 63.41, P